DZIAŁALNOŚĆ IWANA KEDRYNA RUDNICKIEGO NA RZECZ POROZUMIENIA UKRAIŃSKO-POLSKIEGO LAT 30. XX WIEKU W II RP - Wójtowicz, Sylwia (Studia Ukrainica Posnaniensia, 2016)
In the article the activities of the Ukrainian writer and politician of the interwar period Ivan Kedryn Rudnicki are discussed. As a member of UNDO (Ukrainian National Democratic Alliance) and journalist of the newspaper “The Dilo” Rudnicki stood on guard of the interests of the Ukrainians, living in the Second Polish Republic. In the first half of the 30s he was one of the animators of standardization policy in very diffi cult Polish-Ukrainian relations.